Social responsibility and individual freedom in axiosphere of modern information society - Кунденко, Я. М.; Гаплевська, О. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article considers freedom and responsibility as the conditions of existence the social relations, and their interaction in the context ofvalue orientations of person in the contemporary information society. In analyzing of scientific achievements conclusion is that the freedomand social responsibility of person is not an external factor of his being, but is a necessary condition for existence of society.